Future internet technologies and trends : First International Conference, ICFITT 2017, Surat, India, August 31 - September 2, 2017, Proceedings /: First International Conference, ICFITT 2017, Surat, India, August 31 - September 2, 2017, Proceedings. ([2018]) - Unknown
No abstract available